Percepción de los egresados del programa de licenciatura en educación física y deportes de la universidad del Quindío en relación a la calidad de la formación recibida (2015)
• The present study aims to study the perceptions of graduates of Bachelor's degree in physical education and sports at the University of Quindio in terms of the quality of the training received. Working with a descriptive quantitative approach to transverse cutting, using a survey designed by the academic Vice Presidency 'survey aimed at graduates' to collect data; who left this work main conclusions were that most of the graduates surveyed say that the education received in the process of undergraduate bring in their life project and high levels of development and acquisition of skills assessment and as well as the greatest strengths of its achievements in fields of training: in research, biomedical, educational and sports; and the quality of teachers to be the main pillars of the program. Rescuing in teachers of the program commitment, the suitability and constant training readiness as: specialization, master's degree, doctorate, etc.) In this way offer the security students have good quality training. Respondents at the time of identify weaknesses of the institution designates precisely the curriculum where manifest lack of recreational contents, expand the curriculum or change materials which do not have much impact in the context of the city as softball, is strengthen the pedagogical practices doing them since the first semesters. Now, the second biggest weakness of the programme is, in the opinion of the graduates the quality of training being delayed by the lack of laboratories, sports deployment and infrastructure to carry out the educational process